(untitled) (Productivity, 2020)
This research aims to determine whether the marketing mix (product, price, promotion, and place) influences the decision to purchase drinks at Halu Kopinspirasi. This study gave questionnaire to 100 respondents who had bought coffee drinks at Halu Kopinspirasi. This study uses multiple linear regression analysis which shows the marketing mix (product, price, promotion, and place) simultaneously influences the purchasing decision. product variables on influence on purchasing decisions. Variable prices, promotions, and partial places do not favor purchase decisions. Halu owners try to encourage him to improve prices, promotions, and places to attract buyers. And maintain its products, in order to maintain its buyers.Â